Pengaruh Tekanan Kerja Terhadap Kinerja Pegawai Di Lembaga Pemasyarakatan Kelas Iia Pematangsiantar - Johan Sitorus; Padmono Wibowo (CV. KAMPUS AKADEMIK PUBLISING, 2023)
Efforts to improve employee work results are by paying attention to work stress. Stress can occur in every human individual at any time because stress is also an unavoidable part of human life. People often experience stress if they cannot adjust their desires to facts either from within or from outside themselves. This research aims to find out how much influence work stress has on employee performance at the class IIA Pematangsiantar Penitentiary. This research uses quantitative methods, using questionnaires as a technique for obtaining data and the total number of samples in this research is 37 employees. The calculations in this research are that researchers use SPSS software which can show the relationship between the two variables, and how much influence work stress has on workers' work. The results of this research show that work stress on employee work shows strong positive results, because the regression coefficient value has a negative sign, namely 0.27. Based on the results of the analysis of managed data, it can be concluded that the influence of work stress on employee performance is at a strong correlation level, namely 0.75, which means that the level of influence of work stress on working employees is 75%, while 25% is influenced by other variables not examined.